An all-solid-state biocompatible ion-to-electron transducer for bioelectronics. Issue 2 (17th January 2018) - Sheliakina, M.; Mostert, A. B.; Meredith, P.
Abstract : The first all solid state organic electrochemical transistor based upon the skin pigment melanin. Abstract : Reported here is an all-solid-state organic electrochemical transistor based on the biopolymer melanin. The underlying mechanism is demonstrated using a unique hydration dependence protocol and explained using an adapted double capacitor model. The demonstration of an all-solid-state bioelectronic prototype is critical for the development of miniaturised bioelectronic logic.